Foresight for income and employment: What can we learn for agricultural research for development - Kruseman, Gideon K.; Dermawan, A.; Diagne, M.; Enahoro, Dolapo K.; Frija, A.; Gatto, M.; Gbegbelegbe, Sika; Komarek, A.M.; Mausch, K.; Mottaleb, K.; Nedumaran, S.; Tesfaye, K.; et al. (Center for Open Science, 2021)
Challenges related to poverty, hunger, nutrition, health, and the environment are widespread and urgent. One way to stress the urgency of making the right decisions about the future of the global food systems now is to better understand and more clearly articulate the alternative scenarios that food systems face. Developing, synthesizing, and presenting such alternatives to decision makers in a clear way is the ultimate goal of e CGIAR Foresight team.